Commercialization as a Factor Influencing Economic Science - Jan KOMOROWSKI (Communications of International Proceedings, 2020)
Commercialization as a factor influencing the economic science When searching for threats to research at the interface between theory and practice in the modern world, we may not overlook commercialization. Research commercialization is part of the current surveys devoted to the conditions of the evolution of modern science. Typically, commercialization is seen positively, as a main factor, which improves economic growth. Market mechanism is believed to have the power to boost research development by adapting it to market needs and opportunities, better use of research benefits and gains, mobilizing investment, etc. The impact of market mechanism is also used to provide adequate valuation and allocation of resources. We must bear in mind that the impact of commercialization on research is much deeper and multilateral and it produces much more complex consequences to research and economy.
Keywords: Commercialization of research; evaluation of intellectual value; utility gap; privatization of scientific knowledge.